Writing Quantum Entanglement into International Relations: Temporality, Positionality, and the Ontology of War. (September 2020) - McIntosh, Chris
AbstractLaura Zanotti's Quantum Entanglements offers something unique to the burgeoning literature surrounding quantum physics, social science, and international relations. Rather than emphasizing the materiality of the science, it expressly aims its focus toward those already engaged in relationality, critical practice, and the politics of ontologies–even/especially for those not especially interested in science qua science. Zanotti's book calls for a fundamental rethink of the widespread influence of substantialism, even in the places that self-identify as rejecting it as a philosophical position. By positioning Newtonian thought as a metaphor, rather than a mimetic representation of scientific reality, Quantum Entanglements widens the applicability of quantum thinking to areas seemingly far removed from these debates. This article engages Zanotti's work by reading her insights into three different areas of IR scholarship where her ideas could be particularly useful –temporality, scholarly positionality, and the ontology of war. For each I suggest conceptual developments building on the critique of substantialism and emphasis on quantum entanglement. These developments emphasize the inextricability and ontological challenge of entanglement, as well as centering intellectual and political modesty and human/non-human relationality as ways forward for thinking international politics.